2009
DOI: 10.1080/02643290903478549
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of species, volume, and belief in patients with Alzheimer's disease: The issue of domain specificity and conceptual impairment

Abstract: Two studies investigated whether patients with Alzheimer’s disease (AD) suffer high-level and category-specific impairment in the conceptual domain of living things. In Study 1, AD patients and healthy young and healthy elderly controls took part in three tasks: the Conservation of Species, Volume, and Belief. All 3 tasks required tracking an object’s identity in the face of irrelevant but salient transformations. Healthy young and elderly controls performed at or near ceiling on all tasks. AD patients were at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 81 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…Relevant findings include that animist responses are found in healthy young adults under speeded conditions (Goldberg & Thompson‐Schill, ), that is, when executive processes such as inhibition have insufficient time to operate. In addition, several studies of healthy elderly adults and mildly impaired patients with AD have revealed that the AD patients resemble preschoolers on the same battery of biology tasks used here (Zaitchik & Solomon, ,, ). Even the healthy elderly controls made some errors never seen in young adults.…”
Section: Discussionmentioning
confidence: 68%
“…Relevant findings include that animist responses are found in healthy young adults under speeded conditions (Goldberg & Thompson‐Schill, ), that is, when executive processes such as inhibition have insufficient time to operate. In addition, several studies of healthy elderly adults and mildly impaired patients with AD have revealed that the AD patients resemble preschoolers on the same battery of biology tasks used here (Zaitchik & Solomon, ,, ). Even the healthy elderly controls made some errors never seen in young adults.…”
Section: Discussionmentioning
confidence: 68%
“…Note that this proposal—and the logic that it shares with second-language learning—does not solely apply to the counterintuitive concept of natural selection, although it is the case study here. Response competition between formal scientific understandings and intuition-based misconceptions have now been documented across numerous scientific-knowledge domains using a variety of paradigms, including neuroimaging studies (Goldberg & Thompson-Schill, 2009; Petitto & Dunbar, 2009; Shtulman, 2017; Zaitchik & Solomon, 2009). In short, if the primary goal of formal scientific education is, ultimately, to cultivate students’ abilities to accurately represent and productively generalize canonical scientific knowledge, then it makes sense to initiate coherent mechanistic teaching of foundational but easily misconceived principles earlier rather than later.…”
Section: Evidence Of Conceptual Coexistencementioning
confidence: 99%
“…(For example, patients might have trouble identifying a zebra as a zebra rather than a horse, but not as an animal rather than a vegetable.) Recently, however, Zaitchik and Solomon69–71 raised doubts about this claim that impairment is limited to lower level concepts. Arguing that traditional neuropsychological methods are not really designed to explore the integrity of the domain at its theory level,71–73 they used well‐established methods from developmental psychology to explore the integrity of folkbiology in a group of elderly patients with Alzheimer's disease (AD).…”
Section: Neuropsychology and Folkbiologymentioning
confidence: 99%